Tai Timu, Tai Pari, the ebb and flow of the tides: working with the Waimatā from the Mountains to the Sea - Anne Salmond; Gary Brierley; Dan Hikuroa; Billie Lythberg (New Zealand Journal of Marine and Freshwater Research, 2022)
This paper emerges from a Marsden project, Let the River Speak, focused on the Waimatā River in Gisborne, bringing insights from mātauranga and wānanga together with a wide range of disciplines to produce innovative and engaged understandings of ki uta ki tai‐the life of rivers from the mountains to the sea. In Te Ao Māori, waterways are relational knots/nodes/strands in a meshwork of whakapapa that arises from exchanges between earth and sky, land and sea. This approach acknowledges the relations between the atmosphere, surface water and groundwater, vegetation cover, land use, water quality and quantity, the sea, plants, animals, micro‐organisms and people; and rivers as beings in their own right, with their own rights. Let the River Speak is codeveloped with the river by a team including iwi researchers, scholars from earth system science, geomorphology, microbiology and infectious diseases, forest ecology, anthropology, creative practice, and business studies. It is holistic, working across different knowledge systems to understand the full complexity of waterways in relationship with people and other life forms over time. At the same time, it is hopeful, providing a relational framework for actions to restore river and estuarine communities to a state of ora (health, well‐being, flourishing).